Enhanced phenylpropanoid metabolism underlies resistance to Fusarium oxysporum f. sp. vasinfectum race 4 infection in the cotton cultivar Pima-S6 (Gossypium barbadense L.) - Jonathan Odilón Ojeda-Rivera; Mauricio Ulloa; Francisco G. Pérez-Zavala; Héctor-Rogelio Nájera-González; Philip A. Roberts; Lenin Yong-Villalobos; Himanshu Yadav; Ricardo A. Chávez Montes; Luis Herrera-Estrella; Luis Herrera-Estrella; Damar Lopez-Arredondo (Frontiers in Genetics, 2024)
Introduction:Fusarium oxysporum f. sp. vasinfectum (FOV) race 4 (FOV4) is a highly pathogenic soil-borne fungus responsible for Fusarium wilt in cotton (Gossypium spp.) and represents a continuing threat to cotton production in the southwest states of the United States, including California, New Mexico, and Texas. Pima (G. barbadense L.) cotton, which is highly valued for its fiber quality, has been shown to be more susceptible to this pathogen than Upland (G. hirsutum L.) cotton. Still, some Pima cultivars present resistance to FOV4 infection.Methods: To gain insights into the FOV4-resistance mechanism, we performed comparative transcriptional and metabolomic analyses between FOV4-susceptible and FOV4-resistant Pima cotton entries. FOV4-resistant Pima-S6 and FOV4-susceptible Pima S-7 and Pima 3-79 cotton plants were infected with FOV4 in the greenhouse, and the roots harvested 11 days post-infection for further analysis.Results: We found that an enhanced root phenylpropanoid metabolism in the resistant Pima-S6 cultivar determines FOV4-resistance. Gene-ontology enrichment of phenylpropanoid biosynthesis and metabolism categories correlated with the accumulation of secondary metabolites in Pima-S6 roots. Specifically, we found esculetin, a coumarin, an inhibitor of Fusarium’s growth, accumulated in the roots of Pima-S6 even under non-infected conditions. Genes related to the phenylpropanoid biosynthesis and metabolism, including phenylalanine ammonia-lyase 2 (PAL2) and pleiotropic drug resistance 12 (PDR12) transporter, were found to be upregulated in Pima-S6 roots.Discussion: Our results highlight an essential role for the phenylpropanoid synthesis pathway in FOV4 resistance in Pima-S6 cotton. These genes represent attractive research prospects for FOV4-disease resistance and breeding approaches of other cotton cultivars of economic relevance.